The Religious and Ethnic Issues in Thailand: Impacts to Sustainability in South East Asian and Implications for Vietnam - Chieu, Nguyen Van (Advances in Social Sciences Research Journal, 2018)
Ethnic and religious conflicts in Thailand is one of the complex political phenomenons which bring the significant impacts to the region of South East Asia, incluing Vietnam. Over the past decades, the Government of Thailand has adopted a number of policies to tackle ethnic-religious conflicts and regard them as an internal affair of this country. However, in the openness of the region, such conflicts has gradually become a concern for those countries in the rgion. This has forced countries in the region to have critical research, assessment and interpretation in order to propose the appropriate responded policies to maintain the sustainability and security of the region in general and of each country in particular.